Euglycemic diabetic ketoacidosis caused by dapagliflozin: A case report. Issue 25 (June 2018) - Chou, Yu-Mou; Seak, Chen-June; Goh, Zhong Ning Leonard; Seak, Joanna Chen-Yeen; Seak, Chen-Ken; Lin, Chih-Chuan
Abstract: Rationale: Diabetic ketoacidosis is a serious and potentially life-threatening acute complication of diabetes mellitus (DM). Euglycemic diabetic ketoacidosis (eDKA) is however challenging to identify in the emergency department (ED) due to absence of marked hyperglycemia, often leading to delayed diagnosis and treatment. eDKA has been recently found to be associated with sodium-glucose cotransporter 2 (SGLT2) inhibitors, one of the newest classes of antidiabetics, though there are very limited reports implicating dapagliflozin as the offending agent in ED patients. Here we report a type 2 diabetic patient who presented to the ED with eDKA secondary to dapagliflozin administration. Patient concerns: A 61-year-old Asian female with underlying type 2 DM presented to our ED with body weakness, dyspnea, nausea, vomiting, and mild abdominal pain for the past 2 days. These symptoms were preceded by poor oral intake for 1 week due to severe toothache. Dapagliflozin was recently added to her antidiabetic drug regimen of metformin and glibenclamide 2 weeks ago. Diagnoses: Arterial blood gases showed a picture of severe metabolic acidosis with an elevated anion gap, while ketones were elevated in blood and positive in urine. Blood glucose was mildly elevated at 180 mg/dL. Serum lactate levels were normal. Our patient was thus diagnosed with eDKA. Intervention: Our patient was promptly admitted to the intensive care unit and treated for eDKA through intravenous rehydration therapy with insulin infusion. Outcomes: Serial blood gas analyses showed gradual resolution of the patient's ketoacidosis with normalized anion gap and clearance of serum ketones. She was discharged uneventfully on day 4, with permanent cessation of dapagliflozin administration. Lessons: Life-threatening eDKA as a complication of dapagliflozin is a challenging and easilymissed diagnosis in the ED. Such an ED presentation is very rare, nevertheless emergency physicians are reminded to consider the diagnosis of eDKA in a patient whose drug regimen includes any SGLT2 inhibitor, especially if the patient presents with nausea, vomiting, abdominal pain, dyspnea, lethargy, and is clinically dehydrated. These patients should then be investigated with ketone studies and blood gas analyses regardless of blood glucose levels for prompt diagnosis and treatment.